Occurrence and age composition of Paralabidocera antarctica (Calanoida, Copepoda) under the fast ice near Syowa Station, Antarctica - Tanimura, Atsushi; Fukuchi, Mitsuo; Ohtsuka, Hideaki (1984)
P(論文) A year-round observation of Paralabidocera antarctica, an endemic copepod in the Antarctic, was done near Syowa Station, Antarctica, from January 1982 to January 1983. P. antarctica occurred in the spring to the summer seasons between late September and late January and was very abundant while the phytoplankton biomass was high. The P. antarctica population which appeared in late September to early November was composed of copepodite stages I, II and III. Developmental stage progressed from middle November to middle December. In middle December, the P. antarctica population consisted mostly of adults with a few individuals of copepodite stage V. After late December it was occupied by adults only, while adult females were bearing the spermatophores commonly. P. antarctica seemed to have one generation in a year. departmental bulletin paper